STRENGTH DEVELOPMENT CHARACTERISTICS AND MICROSTRUCTURAL PROPERTIES OF HIGH STRENGTH CONCRETE HAVING OPTIMAL NANOSILICA DOSAGE - Adamu, Ibrahim Muhammad; Kaura, J. M.; Lawan, A.; Ocholi, Amana (FUDMA JOURNAL OF SCIENCES, 2020)
The use of Supplementary Cementitious Materials (SCM) to improve the performance of concrete is gaining popularity globally. This study investigated the tensile and compressive strengths development, microstructural properties and cement hydration reaction for High Strength Concrete (HSC) having optimal dosage of an SCM called Nanosilica (nS). The Optimal Nanosilica Dosage (ONSD) in HSC was determined to be 1 % by weight of cement using compressive strength test. The influence of ONSD on the properties of the HSC was investigated using compressive strength test, splitting tensile strength test, Scanning Electron Microscopy (SEM) and Energy Dispersion Spectroscopy (EDS). Results revealed that addition of ONSD led to 17.10 % and 20.52 % respective increase in compressive and tensile strengths of HSC at 7 days of curing. There was 15.41 % and 9.60 % respective increase in characteristic cylindrical compressive and axial tensile strengths of HSC determined according to Eurocodes on addition of ONSD. SEM micrographs show better packing density in the High Strength Nano-Concrete (HSNC) at 90days of curing. EDS shows that addition of ONSD in HSC led to formation of more C-S-H gels at 90days of curing, and a corresponding reduction in Ca/Si ratio of the Optimal High Strength Nano-Concrete (OHSNC) to 0.91, a ratio very close to 0.81; the Ca/Si ratio of 14Çº tobermorite C-S-H model reported in literature.
Keywords: Compressive strength, Tensile strength, Optimal high strength nano-concrete, SEM, EDS